PENINGKATAN KOMPETENSI PROFESIONAL KECANTIKAN PADA PEKERJA INDONESIA DI SINGAPURA MELALUI PEMBUATAN LULUR TRADISIONAL PENGANTIN - Neneng Siti Silfi Ambarwati; Mari Okatini Armandani; Nurul Hidayah; Dian Pertiwi Josua (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This study analyzes and reports the competency of beauty workers among Indonesian migrant workers in Singapore through the practice of making traditional bridal scrubs known as Javanese lulur. This study focuses on the cultural significance, education of traditional cosmetic ingredients and lulur making as a traditional beauty treatment rooted in Indonesian beauty heritage through skill development activities for Indonesian migrant workers. The training method to measure the impact of traditional bridal lulur training on skill development is presented in a qualitative descriptive manner. The activities were carried out by combining knowledge, demonstration and individual training aimed at improving employability and integrating cultural identity in the Singaporean beauty industry. The findings of the study revealed that the training could improve technical skills and increase professional confidence in making traditional bridal lulur. The results of this study highlight the importance of integrating cultural heritage into beauty professional development programs, especially for Indonesian migrant workers in the practice and making of traditional cosmetics such as lulur making for Indonesian migrant workers, so that it can preserve culture and potentially become economic empowerment. Keywords: Professional competence of beauty, Traditional Bridal Scrub, Traditional Cosmetics Abstrak Studi ini menganalisis dan melaporkan kompetensi profesional kecantikan di kalangan pekerja migran Indonesia di Singapura melalui praktik pembuatan lulur pengantin tradisional, yang dikenal sebagai lulur Jawa. Penelitian berfokus pada signifikansi budaya, edukasi bahan kosmetika tradisional dan pembuatan lulur sebagai perawatan kecantikan tradisional yang berakar pada warisan kecantikan Indonesia melalui kegiatan pengembangan keterampilan bagi pekerja migran. Metode palatihan guna mengukur dampak pelatihan lulur pengantin tradisional pada pengembangan keterampilan disajikan secara deskriptif kualitatif. Kegiatan dilakukan dengan menggabungkan pengetahuan, demonstrasi dan pelatihan individual yang bertujuan meningkatkan kemampuan kerja dan memadukan identitas budaya dalam industri kecantikan Singapura. Temuan mengungkapkan bahwa pelatihan dapat meningkatkan keterampilan teknis dan mendorong kepercayaan diri profesional dalam berkreasi membuat lulur pengantin tradisional. Hasil penelitian ini menyoroti pentingnya mengintegrasikan warisan budaya ke dalam program pengembangan profesional kecantikan, khususnya bagi pekerja migran dalam praktik dan pembuatan kosmetika tradisional seperti pembuatan lulur bagi pekerja migran, sehingga dapat melestarian budaya dan berpotensi sebagai pemberdayaan ekonomi. Kata Kunci: Kompetensi profesional kecantikan, Lulur Tradisional Pengantin, Kosmetika Tradisional